Philosophy of Sport : International Perspectives. - Hardman, Alun R. (Cambridge Scholars Pub., 2010)
The book Philosophy of Sport: International Perspectives represents the work of some of the leading moral and philosophical academics in the popular practice of sport. All contributors are scholars and researchers in the area of the Philosophy of Sport, a growing area of serious study within universities and colleges across the world. The contributors are also active members of the International Association for the Philosophy of Sport-a worldwide organisation dedicated to the development of t ...